Faktor-Faktor yang Mempengaruhi Kejadian Hiperemesis Gravidarum pada Ibu Hamil di BPM Muliyanti Desa Luengsa Kec. Madat Kab. Aceh Timur Tahun 2023 - Nora Tasnim; Kamelia Sinaga; Imran Saputra Surbakti; Asnita Sinaga; Riza Novianti (Pusat Riset dan Inovasi Nasional, 2024)
Nausea and vomiting are common conditions experienced during pregnancy, especially in the first trimester, and are considered a normal physiological response that occurs in around 50%-80% of pregnant women. However, if this condition worsens and persists, it can develop into hyperemesis gravidarum, a pregnancy disorder that occurs in around 1 in 1000 pregnant women. This condition is at risk of causing dehydration and electrolyte imbalance and acidoketosis. This study aims to analyze the factors that influence the incidence of hyperemesis gravidarum in BPM Muliyanti, Luengsa Village, Madat District, East Aceh Regency in 2023. The type of research is Descriptive Correlation research with a cross-sectional design. The research sample consisted of 36 respondents, who were selected using a sampling technique with Purposive Sampling. Based on the results of the bivariate analysis using the Pearson Chisquare test, it is known that the p-value is 0.028, so it can be concluded that there is a statistically significant relationship between Maternal Parity and the Incidence of Hyperemesis Gravidarum in Pregnant Women in BPM Muliyanti, Luengsa Village, Madat District. East Aceh Regency Drugs in 2023.